Halal Tourism, Cerfication Regulation, and Research Institute Insigh From IMT-GT Countries: A Review: A Review - Aziza, Nurul; Prasnowo, M. Adhi; Khoirul Hidayat (International Journal of Science, Technology & Management, 2020)
The Indonesia-Malaysia-Thailand Growth Triangle) began as an initial effort of liberalization and economic integration in ASEAN. IMT-GT was officially endorsed in 1993, provides a sub-regional framework to accelerate cooperation and economic integration to develop the country's economy. With the increasingly vigorous issue of halal, then established the institution to oversee and provide assurance against halal products. This article explains halal tourism, regulation on halal certification as well as research institute about halal. There are by providing the differences between the three developing countries namely Indonesia, Malaysia and Thailand. Indonesia has regulation about concerning guarantee of halal products regulation UU number 33 year 2014. Malaysia has an advantage in terms of regulations and laws on halal certification, but not so with Indonesia as a country with a majority Muslim population. Indonesia has not made halal certification as a guarantee of food and beverage product safety. Indonesia also has a large and free halal market, clear rules, but in implementation it can be said to be weak. Whereas in Malaysia, halal research is quite strong and shows an increasing trend, public awareness about halal is also strong so that the process of certifying halal products goes synergistically. But in Thailand is still starting steps towards halal research. But on the other hand, producers in Thailand have a high awareness of the importance of producing halal products.